2018
DOI: 10.3390/min8010033
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory and Atomic Force Microscopy Study of Oleate Functioned on Siderite Surface

Abstract: Abstract:Efficiently discovering the interaction of the collector oleate and siderite is of great significance for understanding the inherent function of siderite weakening hematite reverse flotation. For this purpose, investigation of the adsorption behavior of oleate on siderite surface was performed by density functional theory (DFT) calculations associating with atomic force microscopy (AFM) imaging. The siderite crystal geometry was computationally optimized via convergence tests. Calculated results of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Generally, the surface chemistry of a film affects its surface energy. Previous work showed that FeCO 3 possessed a higher surface energy than FeS [52,53]. This is aligned with the time-dependent behaviour of adhesion force observed in Figure 9.…”
Section: The Steel Mic In D Vulgaris-containing Tel and Its Correlati...supporting
confidence: 88%
“…Generally, the surface chemistry of a film affects its surface energy. Previous work showed that FeCO 3 possessed a higher surface energy than FeS [52,53]. This is aligned with the time-dependent behaviour of adhesion force observed in Figure 9.…”
Section: The Steel Mic In D Vulgaris-containing Tel and Its Correlati...supporting
confidence: 88%
“…With the great advantage of DFT calculation based on the intrinsic electronic configurations of atoms, systematic DFT studies have been effectively employed in many fields, such as in the flotation process for revealing interactions between flotation reagents and mineral surfaces [9,10]. Inherent properties, such as adsorption energy, charge transfer, and bond strength are intuitively acquired through the computational data and images [11,12]. Lu et al [5] presented an approach for surface wettability prediction for various polar liquid molecules and solid surface ions based on the interaction energy of the liquid-solid surface.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of molecular, interaction energies, and Mulliken population analysis give a vivid characterization to the sorption mechanism and provide deep insight into the separation process from the aspects of physical and chemical (Rath et al, 2014). In our previous study, the mechanism of depression of hematite and the adsorption mechanism of oleate on siderite were investigated using DFT (Pradip et al, 2002;Li et al, 2018Li et al, , 2019Zhang et al, 2019Zhang et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%